Book Review: Dramatic Exegesis of the Psalms of Ascent: David C. Mitchell, The Songs of Ascents: Psalms 120 to 134 in the Worship of Jerusalem’s Temples. - Daffern, M (SAGE Publications, 2017)
At first glance David Mitchell’s book does not appear mainstream. Yet its pages contain a broad range of explorations of these fifteen psalms, which betrays engagement with many pertinent questions about the Psalms, worship in the Jerusalem Temples, and ancient music. Mitchell’s reading is thorough and eclectic, his thinking is imaginative and novel, and his writing engaging and thought-provoking.